Nutrition knowledge of the elementary school teachers and its implication for health education - Noche, Marcela Alday 1930-
The purpose of this study was to identify the nutrition knowledge of the elementary school teachers of Batangas II and its implications for health education. It revealed the strengths and weaknesses of both the nutrition education program and total school health program thus providing the baseline data for instituting remedial measures for improvement. The normative method of research was employed. The findings showed the need for teachers to enrich and update their nutrition knowledge especially in the topic found least to them.